2007
DOI: 10.1001/archderm.143.5.613
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Correlation of Cutaneous Metastases

Abstract: Setting: Comprehensive cancer center.Patients: Fifty-one patients (21 men and 30 women) with biopsy-proven skin metastases and correlative clinical data.Interventions: Four dermatopathologists reviewed a random mixture of metastases and primary skin tumors. Immunohistochemical studies for 12 markers were performed on the metastases, with skin adnexal tumors as controls.Main Outcome Measures: Clinical characteristics of cutaneous lesions, clinical outcomes, histologic features, and immunohistochemical markers.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
178
4
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(201 citation statements)
references
References 34 publications
13
178
4
6
Order By: Relevance
“…Many physicians consider skin alterations a frequent manifestation of internal disease, at the same time, neoplastic diseases rarely spread to the skin particularly from internal organs [6,[10][11][12]. In our study autopsies revealed only less than 1 % prevalence of skin metastasis among gastrointestinal, lung, hepatobiliary and urogentital tract cancers.…”
Section: Discussioncontrasting
confidence: 45%
“…Many physicians consider skin alterations a frequent manifestation of internal disease, at the same time, neoplastic diseases rarely spread to the skin particularly from internal organs [6,[10][11][12]. In our study autopsies revealed only less than 1 % prevalence of skin metastasis among gastrointestinal, lung, hepatobiliary and urogentital tract cancers.…”
Section: Discussioncontrasting
confidence: 45%
“…[3][4][5][6]10 In studies published by Ivan et al, 4,5 tumors with o25% p63 nuclear staining were considered negative. Thus, with this higher cutoff value, the authors reported a 100% specificity with the majority of the cutaneous metastases being negative for p63, although focal staining was reported in 5 of 14 (36%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Current markers purportedly of utility as diagnostic adjuncts include p63 and D2-40, both reportedly preferentially expressed in the primary sweat gland carcinomas. [3][4][5][6]9,10 However, the utility of these is somewhat conflicting, given that frequent expression of p63 has been shown in 11-22% of metastatic cutaneous adenocarcinomas and that positive staining with D2-40, although focal, may be seen in up to 5% of cutaneous metastases. 3,6,9,10 Others markers cited include calretinin, found to be positive in 64% of primary cutaneous neoplasms and negative in 72% of cutaneous metastases.…”
mentioning
confidence: 99%
See 2 more Smart Citations